Penerapan Pembelajaran Sains dalam Menstimulasi Perkembangan Anak pada Masa Pembelajaran Tatap Muka Terbatas (PTMT) di KB Bintang Kejora - Nurul Azminah, Suhartini; Citrasukmawati, Alfina; Idamulyani, Sri (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2022)
Research on the application of science learning in stimulating children's development during the limited face-to-face learning period at KB Bintang Kejora was motivated by the COVID-19 pandemic situation where teachers must continue to provide learning that facilitates children to explore such as learning science while still paying attention to health protocols. This study aims to describe how the application of science learning in the face-to-face learning period is limited. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation which are analyzed in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the application of science learning is carried out using a simple science experiment method, a maximum of 5 children are involved, and science experiments are carried out independently and individually without grouping in order to keep their distance and avoid crowds.